Distribution of polycyclic aromatic hydrocarbons in snow of Mount Nanshan, Xinjiang. (22nd October 2014) - Lei, Xiaoning; Li, Weiwei; Lu, Jianjiang; Tong, Yanbin; Li, Shanman
Abstract Polycyclic aromatic hydrocarbon (PAH) in snow samples collected from Mount Nanshan (Xinjiang, China) was investigated for eight stations. Fourteen PAHs were detected in these samples. The total PAH concentration ranged from 70.15 ng/L to 155.67 ng/L, with an average of 113.02 ng/L. Human carcinogens, such as fluoranthene, chrysene, benzo(a)pyrene, dibenzo(a, h)anthracene, indeno(1, 2, 3‐cd)pyrene and benzo(ghi)perylene in snow were assessed based on risk quotient. Preliminary assessment showed that these PAHs posed a moderate risk. Component analysis showed that the PAHs found in the snow samples were mainly three‐ring PAHs, which comprised 34.51–90.81% of the total PAHs. Phenanthrene, fluorene and anthracene accounted for 35.08, 11.90 and 11.13% of the total PAHs, respectively. The ΣPAH content increased with the increasing altitude, and the highest concentration of 155.67 ng/L was observed in snow samples from the N7 station, which was located near the top of the mountain. This high PAH concentration in N7 was possibly due to more frequent human activities in the area and long‐distance transportation of PAHs. Isomer ratios were used to determine the possible sources of PAHs in the samples. The results indicate that coal and biomass combustion made a larger contribution than emissions from petroleum consumption. It is therefore of utmost importance to develop new fuels taking the place of coal and to achieve as complete as possible for the burning of carbon‐containing materials.